Emergency remote teaching of didactic in undergraduate Courses in Southern Brazil - Feldkercher, Nadiane (2022)
The pandemic situation has changed the daily life of higher education, demanding new ways of organizing the teaching work. Immersed in this "new" context of education, the present work aimed to analyze, from the perspective of students of undergraduate courses at federal and state universities in Southern Brazil, the teaching of Didactics in a remote emergency way, taking into consideration both the conditions of students for their participation in pedagogical activities and the specificities of the teaching of Didactics. The quanti-qualitative and empirical research used online questionnaires as an instrument for data collection. Our theoretical and analytical base was situated in the field of Didactics. The results of the research point to the challenges faced by the students, among them: the limited technological resources, the instability of the internet, and the financial difficulty to change this situation. We also observed the emotional impact that affected the way students engaged in teaching and learning activities. On the other hand, the students highlight the potential of teaching Didactics remotely, mentioning the importance of incorporating the use of technologies in their training and in their future pedagogical practices, emphasizing that the remote teaching of Didactics changed the mode of interaction between teachers and students and the mediation of the content. These potentialities call Didactics, as a field of knowledge, to build other ways of teaching and learning, expanding the understanding of the educational and pedagogical use of technologies without incurring in instrumentalization